Experiences with long-term care for geriatric patients by an interprofessional outpatient care approach – a qualitative study - Denise Wilfling; Jona Budke; Nicole Warkentin; Katja Goetz (BMC Geriatrics, 2023)
Abstract Background Outpatient care for geriatric patients is complex and requires the collaboration of different professions for supporting long-term care. Care and case management (CCM) could provide support with that. The long-term care of geriatric patients could be optimized with an interprofessional, cross-sectoral CCM. Therefore, the aim of the study was to evaluate the experiences and attitudes of those involved in the care with regard to the interprofessional design of the care for geriatric patients. Methods A qualitative study design was used. Focus group interviews were conducted with those involved in the care (general practitioners (GP), health care assistants (HCA) as well as care and case managers (CM)). The interviews were digitally recorded, transcribed and analysed by qualitative content analysis. Results Overall, ten focus groups were conducted in the five practice networks with n = 46 participants (n = 15 GP, n = 14 HCA and n = 17 CM). The participants evaluated the care they received from a CCM positively. The HCA and the GP were the primary points of contact for the CM. The close collaboration with the CM was experienced to be rewarding and relieving. Through their home-visitations, the CM gained a deep insight into the homelives of their patients and were thus able to accurately reflect the gaps in the care back to the family physicians. Conclusions The different health care professionals involved in this type of care experience that an interprofessional and cross-sectoral CCM is able to optimally support the long-term care of geriatric patients. The different occupational groups involved in the care benefit from this type of care arrangement as well.